Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376760
|View full text |Cite
|
Sign up to set email alerts
|

"Alexa is a Toy": Exploring Older Adults' Reasons for Using, Limiting, and Abandoning Echo

Abstract: Intelligent voice assistants (IVAs) have the potential to support older adults' independent living. However, despite a growing body of research focusing on IVA use, we know little about why older adults become IVA non-users. This paper examines the reasons older adults use, limit, and abandon IVAs (i.e., Amazon Echo) in their homes. We conducted eight focus groups, with 38 older adults residing in a Life Plan Community. Thirty-six participants owned an Echo for at least a year, and two were considering adoptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 50 publications
(46 reference statements)
7
75
0
Order By: Relevance
“…These findings are in line with several recent research studies that highlight the potential of AI and subsets technologies, such as voice recognition and natural language processing (NLP), to support various healthcare and home assistance applications [17,[47][48][49][50][51][52]. These findings also suggest, in line with [17,24,49,52], that voice activated devices and AI-enabled apps (e.g., chatbots), are expected to play an increasing role in the care and support of older people in the near future. On the other hand, technologies that did not reach consensus, such as exoskeletons and VR/MR/AR, or reached it in a few domains, such as robotics, appear to have more technical and potential acceptability issues.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are in line with several recent research studies that highlight the potential of AI and subsets technologies, such as voice recognition and natural language processing (NLP), to support various healthcare and home assistance applications [17,[47][48][49][50][51][52]. These findings also suggest, in line with [17,24,49,52], that voice activated devices and AI-enabled apps (e.g., chatbots), are expected to play an increasing role in the care and support of older people in the near future. On the other hand, technologies that did not reach consensus, such as exoskeletons and VR/MR/AR, or reached it in a few domains, such as robotics, appear to have more technical and potential acceptability issues.…”
Section: Discussionsupporting
confidence: 89%
“…Some of the main reasons for this are lack of perceived value and positive impact of technology on older people’s quality of life as well as lack of confidence in their digital skills [ 19 , 21 , 22 , 23 ]. For example, a recent study reported that failure to identify essential uses of Alexa (a voice activated device) was one of the main reasons for abandoning its use by older people over time [ 24 ]. Therefore, there is arguably a need to further explore the potential of emerging technologies and highlight their potential uses and benefits for older people.…”
Section: Introductionmentioning
confidence: 99%
“…A new perspective on voice-user interface design could be necessary for VA to engage with endusers with various healthcare needs during a crisis to communicate and exchange health information effectively. At-risk communities who can potentially benefit from VA, such as the elderly, should especially be considered 39,40 . Currently, VAs' user engagement and comprehension may not be optimal with medical communications (e.g., not understanding a command, providing erroneous or misleading content) 41,42 .…”
Section: Readiness Of Technology Providersmentioning
confidence: 99%
“…Although a voice assistant holds great promise to support older adults through its simple speech-based interaction modality, little is known about how older adults perceive and respond to the idea of talking to a device that does not have a graphical user interface. Researchers have recently begun to investigate older adults' use of a voice assistant, but with few exceptions [ 3 ], they produce preliminary or interim reports [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the small size and low contrast of buttons on a mobile display have a significant negative influence on interaction performance [ 5 ]. Another common barrier is related to psychological and mental obstacles, such as negative cognitive perception [ 3 ], technophobia [ 12 ], and lack of self-efficacy [ 4 ]. Older adults especially tend to refuse a new technology due to perceived effort associated with learning [ 13 ] or lack of perceived usefulness [ 14 ].…”
Section: Introductionmentioning
confidence: 99%